2021
DOI: 10.1186/s12931-021-01680-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lung inflammatory response in whole-body compared to nose-only cigarette smoke-exposed mice

Abstract: Background Chronic obstructive pulmonary disease (COPD) is characterized by a progressive and abnormal inflammatory response in the lungs, mainly caused by cigarette smoking. Animal models exposed to cigarette smoke (CS) are used to mimic human COPD but the use of different CS protocols makes it difficult to compare the immunological and structural consequences of using a nose-only or whole-body CS exposure system. We hypothesized that when using a standardized CS exposure protocol based on par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Multiple consolidations may result from the filling of alveoli by inflammatory exudation, suggesting a more severe damage of alveoli and indicating a poor outcome (35). More involvement of opacifications is supposed to be associated with the immunopathological basis that coronavirus could interact with and modify the intracellular environment during infection for the benefit of quickly replicating (36). Since a dysregulated/exuberant innate response is the dominating factor to coronavirus-mediated pathology, it was of great importance to recognize high-risk imaging features that would result in deterioration on initial admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple consolidations may result from the filling of alveoli by inflammatory exudation, suggesting a more severe damage of alveoli and indicating a poor outcome (35). More involvement of opacifications is supposed to be associated with the immunopathological basis that coronavirus could interact with and modify the intracellular environment during infection for the benefit of quickly replicating (36). Since a dysregulated/exuberant innate response is the dominating factor to coronavirus-mediated pathology, it was of great importance to recognize high-risk imaging features that would result in deterioration on initial admission.…”
Section: Discussionmentioning
confidence: 99%
“…We also focused on extrapulmonary abnormalities based on chest CT, finding that larger lymph nodes and coronary calcification also indicated poor outcomes, and those abnormalities could be detectable in the early stage of the disease. Enlarged lymph nodes may be resulted from severe inflammation (36). Coronary calcification may suggest the combination of CVD, which was reported as one of the most common comorbidities in critically ill patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…Standard whole-body smoking exposure we used might induce more severe systemic inflammation and higher serum cotinine levels compared to nose-only exposure. [ 44 ] However, it has previously been shown that lung function and MLI reached the criteria for COPD as reported. [ 45 48 ] Third, we did not test the exact oxygen consumption of each animal.…”
Section: Limitationsmentioning
confidence: 91%
“…Another limitation is that cigarette smoking plus nasal instillation of LPS, although used for modeling COPD for many years, [43] has been plausibly challenged. Standard whole-body smoking exposure we used might induce more severe systemic inflammation and higher serum cotinine levels compared to nose-only exposure [44] . However, it has previously been shown that lung function and MLI reached the criteria for COPD as reported [45–48] .…”
Section: Limitationsmentioning
confidence: 96%
“…It is important to take into account that several methods can be used to deliver CO in the form of cigarette smoke to the mice, namely nose-only exposure or whole-body exposure [59]. Serré et al ( 2021) compared both methods and stated that after 14 weeks of cigarette smoke exposure, the mice receiving it via whole-body exposure had more inflammation in BAL fluid while nose-only exposure led to more bronchial epithelial damage, mucus production, and airspace enlargement [60]. In contrast, Kogel et al (2021), showed also differences between nose-only exposure and whole-body exposure in ApoE -/mice (murine model for atherosclerosis) which might be specific for this mouse strain, where the nose-only mice had more lung inflammation and molecular dysregulation of the respiratory system [61].…”
Section: Carbon Monoxidementioning
confidence: 99%